서로 다른 세 가지 조명에서 중등도 핵경화 백내장 환자가 가지는 대비감도 및 색각 비교 - 윤요셉(Yo Sep Yoon), 이창규(Chang Kyu Lee), 강상욱(Sang Ook Kang), 김상우(Sang Woo Kim) (Daihan angwa haghoi jabji, 2018)
목적: 실생활 영역에서 흔히 사용되는 2가지 조명(형광등, 삼파장 light emitting diode [LED])과 최근 자연광과 가장 가깝도록 개발된 양자점(quantum dot) LED 조명 아래에서 백내장 환자가 가지는 대비감도 및 색각 정도를 비교하고 그 차이를 분석하고자 하였다. 대상과 방법: 백내장 진료를 위해 안과 외래로 내원한 환자 중 안압과 안저 검사상 정상 소견을 보이는 30안을 대상으로 시행하였다. 세극등현미경검사상 피질부 혹은 후극부에 백내장 없이 순수하게 Lens Opacities Classification System, version III (LOCS III)에 따른 nucleus color/opalescence (NO) grade 2에 해당하는 백내장 환자들만을 대상으로 하여 삼파장 형광등, 삼파장 LED, 양자점 LED 조명 아래에서 대비감도 및 색각 검사를 시행하였다. 결과: 삼파장 형광등과 삼파장 LED에 비해 양자점 LED 조명에서의 전체 오차 점수가 통계적으로 유의하게 낮았으며(p<0.05), 3가지 조명에서 모두 타 계열 색상보다 청색 계열의 오차 점수가 상대적으로 높았다. 결론: 백내장 환자의 경우 색각 검사에서 조명에 따라 색감 인지의 차이가 발생하게 되고, 충분하지 못한 조도와 낮은 연색 지수의 조명 속에서는 그 차이가 더욱 심할 것으로 사료된다. 실내 조명을 태양광과 흡사한 광원분포를 가지고, 높은 연색 지수를 가지는 조명으로 대체한다면, 정신생리학적인 이점과 높은 색각 지각으로 보다 나은 삶의 질을 영위할 수 있을 것으로 생각된다. Purpose: To compare the difference of contrast sensitivity and color vision in patients with cataracts under three illuminations (fluorescent light, three-wavelength light emitting diode [LED], and quantum dot LED). Methods: Thirty eyes with normal intraocular pressure and normal fundus of patients who visited the outpatient clinic for the treatment of cataract were included. In patients with cataracts with grade 2 of nucleus color/opalescence according to the Lens Opacities Classification System, version III (LOCS III) and without cataracts in the cortex or posterior pole of the slit lamp examination, contrast sensitivity and color vision test were performed under fluorescent light, three-wavelength LED, and quantum dot LED. Results: The error scores of quantum dot LED were significantly lower than those of fluorescent light and three-wavelength LED (p < 0.05), and the error scores of blue spectrum was relatively higher than those of other colors. Conclusions: In cataract patients, the difference of color sensation occurs due to illumination in color vision test, and it is considered that the degree of color sensitivity is more severe in insufficient illumination and low color rendering index in color vision test. If we replace the indoor lighting with the light source distribution similar to the sunlight and replace it with the illumination with high color rendering index, we can render higher quality of life to cataract patients through psychophysical advantage and high color perception. KCI Citation Count: 0